Patients’ and plastic surgeons’ experiences with an online patient decision aid for breast reconstruction: considerations for nationwide implementation - Jacqueline A. ter Stege; Ellen G. Engelhardt; Leonie A.E. Woerdeman; Hester S.A. Oldenburg; Jacobien M. Kieffer; Daniela E.E. Hahn; Frederieke H. van Duijnhoven; Martine A. van Huizum; Regina The; Klemens Karssen; Marianne Kuenen; Miranda A. Gerritsma; et al. (BMC Medical Informatics and Decision Making)
Abstract Background Women diagnosed with breast cancer undergoing a mastectomy often have the option to undergo breast reconstruction (BR). BR decisions are complex and have considerable impact. We developed a patient decision aid (pDA) to support patients’ BR decision-making. Here, we assess patients’ and physicians’ use of the BR pDA and their views on the barriers and facilitators for widespread implementation. Methods Participants completed a questionnaire, and back-end data of the pDA was analyzed. Results Of 116 eligible patients, 113 patients accessed the BR pDA (median age: 50 years and 50% were highly educated. Most patients (72%) were satisfied with the pDA and 74% would recommend the BR pDA to other women facing the same choice. Patients’ preferences regarding how much, what kind and how to present information varied. Plastic surgeons (N = 22; 71% response) were satisfied with the pDA. Their key factors for implementation included the perceived match between information and clinical practice, costs, impact on patients, and support from peers and management for the tool. Conclusions As the BR pDA was highly valued by its end users, the identified factors for implementation should be taken into account.